Tests and criteria for assessing the anaerobic workability of sprinter athletes - Samborskiy, A. G.; Severin, S. N.; Nikolaeva, E. S.; Nesterenko, G. L. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the effect of multiple maximum power exercises on the anaerobic performance of sprinters.